Analisis Pendapatan dan Faktor Produksi Usahatani Padi Sawah Tadah Hujan Di Desa Allaere Kecamatan Tanralili Kabupaten Maros - Nuryanti B; Mohammad Anwar Sadat; Arifin Arifin (Jurnal Agribis, 2024)
Income is the acquisition that comes from the costs of production factors or productive services. This definition shows that income is all gains, both originating from production factor costs and the total output generated for all production in an economy within a certain period. Production can be interpreted as an activity that can bring benefits or profits as well as the value of goods and services. In another context, production is referred to as an effort to obtain wealth by utilizing natural resources which is carried out by humans. This research was conducted in Allaere Village, Tanralili District, Maros Regency when this research was conducted for two months from March to April. The purpose of this study was to determine the Income Analysis and Production Factors of rainfed lowland rice farming in Allaere Village, Tanralili District, Maros Regency. This study uses data collection techniques with direct observation and questionnaires. The population in this study was 30 people. Because of the large number of farmers, the samples used as respondents in this study were primary data and secondary data.